2017
DOI: 10.1093/geronb/gbw170
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits and Cognitive Impairment Risk Among Oldest-Old Chinese

Abstract: Dietary habits might profoundly impact cognitive functioning among the oldest-old Chinese. This work has limitations pertaining to study design and measure. Future work adopting experimental design and refined dietary measures is warranted to confirm these findings and inform public nutrition practices aiming at preventing cognitive decline among the oldest-old Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 49 publications
4
35
0
1
Order By: Relevance
“…A Chinese longitudinal survey with 4749 cognitively intact adults aged 80 or older found that, compared with those who rarely or never consumed fruit, vegetables, meat, and soybean-derived products, participants consuming such products almost every day were 21, 25, 17, and 20% less likely to develop cognitive impairment, respectively. However, the consumption of fish, eggs, salt-preserved vegetables, tea, and garlic was not associated with cognitive impairment [ 35 ].…”
Section: Observational Epidemiological Studiesmentioning
confidence: 99%
“…A Chinese longitudinal survey with 4749 cognitively intact adults aged 80 or older found that, compared with those who rarely or never consumed fruit, vegetables, meat, and soybean-derived products, participants consuming such products almost every day were 21, 25, 17, and 20% less likely to develop cognitive impairment, respectively. However, the consumption of fish, eggs, salt-preserved vegetables, tea, and garlic was not associated with cognitive impairment [ 35 ].…”
Section: Observational Epidemiological Studiesmentioning
confidence: 99%
“…The 1946 British birth cohort study also found that higher GI diet at the age of 53 years was associated with lower episodic memory and processing speed at the age of 69 years, although these associations did not remain significant after adjustment for education and cognitive abilities at the age of 15 years [45]. In the Chinese Longitudinal Health Longevity Survey, consumption of sugar "almost every day" was associated with a 17% increase in the risk of cognitive impairment during the 15-year follow-up [46].…”
Section: Discussionmentioning
confidence: 87%
“…In the baseline survey, garlic consumption habits were determined using a brief food frequency questionnaire that has been shown to be effective in assessing the risk of functional performance and mortality [18,20,21]. Participants were asked two questions: “How often do you currently consume garlic?” and “How often did you consume garlic when aged 60 years?”.…”
Section: Methodsmentioning
confidence: 99%
“…Octogenarians, nonagenarians, and centenarians have different risks of morbidity and mortality; thus, we performed analyses among the three age groups separately. Covariates, including demographic variables, socioeconomic status, dietary behaviors, collected using the brief food frequency questionnaire [18,20,21], health practices, functional performance measured using the Katz scale and the Chinese version of the mini-mental state examination (MMSE) were considered for analysis [23,24,25]. On the basis of previous findings in epidemiologic or clinical studies, in our data analyses we adjusted for a number of confounding factors associated with mortality or garlic consumption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation